A simple indentation technique for identifying localized liquefaction of the vitreous body. (2nd December 2021) - Chen, Duo; Liu, Xiaoyu; Geng, Xiaoqi; Huo, Hongqiang; Dong, Ying; Tang, Min; Tang, Zhili; Qiao, Xiaofeng; Fan, Yubo
Abstract: Identification of vitreous liquefaction (VL) is important for investigating some eye pathologies related to changes in the mechanical properties of the vitreous, such as posterior vitreous detachment or retinal detachment. However, because of the extremely high-water content, characterization of the structural and mechanical properties of the vitreous remains a challenge. In the current study, a simple indentation test was performed on the fresh vitreous, partially liquefied vitreous and water, using a mechanical testing machine with a high-precision load cell. Pressure loads on the indenter changing with time for different samples were obtained to characterize their mechanical properties. VL identification was achieved based on a comparison of relative differences in some typical mechanical parameters (e.g. the pressure at the moment of the insertion ( P 0 ), the pressure at the steady mechanical state ( P ∞ ) and the time when the pressure on the indenter declined to one half the initial value ( t 1/2 )) between 1) partially liquefied vitreous and fresh vitreous samples and 2) partially liquefied vitreous and water samples. The results indicated that P 0 of the partially liquefied vitreous was almost half that of fresh vitreous ( p  < 0.05) and approximately 1.5 times that of water ( p  < 0.05). t 1/2 of the partially liquefied vitreous was approximately 1.4 times higher than that of fresh vitreous ( p  < 0.05) and approximately 80% of that of water ( p  < 0.05). It is concluded that P 0 and t 1/2 can be used as indicators to identify localized liquefaction of the vitreous.